(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The following article, “Building Men on the Mat,” reviews the historic relationship between American popular culture and combat arts. The article utilizes archival material from the 18th through the 20th centuries, as well as analyses from relevant social science literature, to demonstrate that the martial arts are integral to American society and are not ad hoc additions to contemporary popular culture. Specific fighting arts discussed include practices such as fencing, cudgel fighting, wrestling, bare-knuckle boxing and judo.